People's Republic of China-Hong Kong Special Administrative Region : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper reviews medium-term fiscal challenges for Hong Kong Special Administrative Region (Hong Kong SAR). It focuses on key considerations that need to be evaluated when formulating a medium-term reserves policy in the face of fiscal challenges, such as accommodating future spending pressures and revenue fluctuations. The broad conclusion of the paper is that fiscal reserves will likely remain an important feature of future fiscal policy. The paper also discusses more general aspects of Hong Kong SAR's economy's competitiveness, and the outlook for Hong Kong SAR's financial center.